Three-dimensional guidance method with course modification for altitude shaping in endoatmospheric interception - Cho, Namhoon (Institute of Electrical and Electronics Engineers (IEEE), 2023)
This study presents a three-dimensional guidance law for the interception of an endoatmospheric target. The proposed method takes an empirical design approach which first specifies the structure of the lateral acceleration command as that of a linear optimal guidance law for zero-effort-miss nullifcation. Then, the direction of pursuit and the guidance gain are designed in accordance with the physical understandings of the motion characteristics of an aerodynamically-controlled interceptor. More specifically, the proposed method induces an intentional increase in the flight altitude around the initial phase while respecting the maximum altitude constraint, all of which are realised through modification of the desired flight path angle in the vertical plane. The proposed guidance method does not rely on explicit definition of design elements such as engagement planes, guidance phases, complicated time-to-go estimation, and waypoints. Moreover, the proposed design approach of modifying the desired course based on the collision courses naturally facilitates smooth handover to the terminal phase near the collision condition. Numerical simulation shows that the proposed guidance method is effective in intercepting a nonmanoeuvring target over a wide range of engagement conditions to the target in comparison to the existing guidance laws developed for homing and midcourse flight.
Keywords: course modification; final speed; guidance; interception; three-dimensional